2008
DOI: 10.1007/s00467-007-0541-z
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological and functional changes of the peritoneal membrane during long-term peritoneal dialysis

Abstract: In long-term peritoneal dialysis (PD) morphological and functional changes of the peritoneal membrane are common. Sub-mesothelial fibrosis, angiogenesis and vasculopathy are typical histomorphological alterations of the peritoneal membrane, which, to a certain degree, are induced by uremia and recurrent peritonitis. The most important causative factor, however, represents the chronic exposure to PD solutions. Glucose, glucose degradation products and advanced glycation end-products (AGEs) via different pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 42 publications
5
52
0
1
Order By: Relevance
“…[1][2][3]5,10 As similar to our study, in a rat model for PD, it was seen that there was an increase in submesothelial thickness and number of inflammatory cells and vessels in the peritoneum after receiving PD fluid with 3.86% glucose by a dialysis catheter for 5 weeks. 11 Williams et al 10 evaluated peritoneum of the * # § x + Figure 4.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…[1][2][3]5,10 As similar to our study, in a rat model for PD, it was seen that there was an increase in submesothelial thickness and number of inflammatory cells and vessels in the peritoneum after receiving PD fluid with 3.86% glucose by a dialysis catheter for 5 weeks. 11 Williams et al 10 evaluated peritoneum of the * # § x + Figure 4.…”
Section: Discussionsupporting
confidence: 67%
“…Our findings indicated that chronic PD increase inflammation. 2,3,12,13 In the stem cell treatment, several labeling methods were used to determine whether tissue regeneration is driven by the effect of exogenous stem cells. [14][15][16] In our study, GFP labeling was employed and it was seen that GFP-labeled MSC was present in the mesothelium line at immunofluorescent microscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term PD frequently produces morphological and functional changes of the peritoneum, making continuation of PD difficult. [4][5][6][7][8] Moreover, progression of peritoneal injury causes serious complications, such as encapsulating peritoneal sclerosis. 9) Therefore, it is necessary to evaluate peritoneal injury at an early stage and develop appropriate treatments for peritoneal injury.…”
mentioning
confidence: 99%
“…4) A reason for this is that long-term PD frequently produces morphological and functional changes of the peritoneum, which leads to discontinuation of PD. [5][6][7][8][9] Moreover, progression of peritoneal injury causes serious complications, such as encapsulating peritoneal sclerosis (EPS). 10) Since therapeutic treatments for peritoneal injury and EPS have yet to be established, 11,12) patients are forced to switch from PD to HD when peritoneal injury occurs.…”
mentioning
confidence: 99%